Dexmedetomidine Related Polyuria and Hypernatremia in Intensive Care Unit. - Dilawar, Mubashar; Riaz, Muhammad Mohsin; Sabir, Omer; Basit, Muhammad Bilal (Pakistan Journal of Kidney Diseases, 2021)
Dexmedetomidine is commonly used sedative nowadays. It’s being used as an anesthetic for surgical procedures and frequently being used in ICU Settings for sedation, and analgesia. Dexmedetomidine is a highly selective, alpha-2 agonist that also blocks arginine-vasopressin release. Dexmedetomidine is suspected to cause diabetes insipidus leading to polyuria and hypernatremia. We report a case of Diabetes Insipidus associated with use of dexmedetomidine.